Bile Acid Nanoparticles - An Emerging Approach for Site Specific Drug Targeting - Suvarna, Vasanti; Sawant, Niserga; Jadhav, Pradnya; Desai, Namita (Current Nanomedicine, 2024)
Bile acids, a group of steroidal acids present in the bile act as biological surfactants and ligands for bile acid transporter proteins for signalling molecules to perform various paracrine and endocrine functions. The enterohepatic circulation of bile acids can be exploited to develop attractive drug delivery approaches with improved targetability of facial amphiphiles and enhanced drug bioavailability by improving absorption and metabolic stability. The effectiveness, safety and targetability of nanoparticles conjugated with bile acids and salts have been discussed in the present review. Various modifications of bile acids promoting absorption and oral bioavailability of drugs for treatment of various disease conditions such as cancer, diabetes and psychosis has also been discussed. Additionally, neuroprotective effect of bile acids and salts has demonstrated utility in various neurodegenerative disorders. Nanoparticles based on bile acids and salts represent an area of emergent interest due to their unique and modifiable properties for improving effectiveness of drugs.
Keywords: Bile acid